A fotografia como instrumento de intervenção clínica junto a pacientes psicóticos - Andrade, Paulo Antonio da Silva (2010)
The present study investigated using two clinical cases, some of the potentialities of the use of photography as a tool in clinical intervention with schizophrenic patients during the hospitalization period. Using Winnicott s contributions and his concepts, especially the concepts of potential space and mirror function. The photographic act will be taken as an interventive-interpretative procedure, exploring its specular, presentative and iconic aspects. The work showed that this procedure has great effects on the patient s creative playing area, body image and the existential field